Tax and spend, spend and tax, fiscal synchronisation or institutional separation? Examining the case of Greece - Christian Richter; Paparas Dimitrios (Romanian Journal of Fiscal Policy (RJFP), 2013)
One of the most controversial issues in public finance and macroeconomics is the nature of the relationship between government spending and revenues. The debate between economists and politicians has been emphasised recently because of the increased budget deficits and defaults in many developed and developing countries. Many economists (Friedman, 1978; Payne, 1997; Darrat, 1998; Albatel, 2002) argued that it is very important to investigate whether the government spending determines the revenues and/or whether government revenue determines the government spending. We are applying an empirical analysis of the spend-tax or tax-spend hypothesis, in order to identify the direction of the causality between government spending and revenues in Greece for the period 1833-2009, a period of industrialisation, urbanisation, increased growth, increased government spending, and enormous budget deficits during the last decades and a serious problem with the public debt. In order to investigate the relationship between government revenues and spending we used the Dickey and Fuller (1979) and Phillips and Perron (1988) unit root tests, the Chow (1960) test and Zivot and Andrews (1992) unit root tests which allow structural changes, the Johansen (1988) cointegration approach and finally the Granger (1969) causality tests. We found strong evidence of long-run relationship between government spending and revenues. Additionally, we used the Granger-causality test which indicates that the causality runs from spending to revenues, thus support of the spend-tax hypothesis. The spend-tax hypothesis maintains that a political system somehow determines how much to spend and then makes the adjustments in tax policy and revenue sources in order to finance the government spending so limitations in spending will be effective for the economy of Greece, but no one could argue that limitations of taxation will be ineffective. It is very important for Greek government to identify the causal direction between government spending and tax revenues, because the direction of causality provides useful insights into how the country can manage their unsustainable budget deficits in the future.
Keywords: C01; C12; C22; E61; E62; E63; H0; H61; 330; Government Spending; Government Revenues; Applied Economics; Greece; Spend-Tax Hypothesis